Monthly availability of underground phytomass in different compartments of a Poa ligularis grassland (Semiárida, 2020)
This work has been done in the Ranch La Baya Vieja. Dpto. Toay, province of La Pampa, to determine the dry weight of deep roots (0-20 and 20-40 cm) and crowns of a grassland of Poa ligularis and Piptochaetium napostaense in winter time, and Bothriochloa springfieldii and Rhynchosia senna in summer time. Along a year and every thirty days we took samples to determine the dry weight of roots and crowns. The total average weight of the roots (0-20 cm) was 1869.8 gMS/m2. The roots (20-40 cm) showed an annual total average weight of 623.2 gMS/m2. At a depth of 20 cm we found 75% of the root volume. The remaining 25% was found at a depth between 20-40 cm. The crowns reached an average weight of 218.7 gMS/m2.